Efektifitas Manajemen Zakat Pada Badan Amil Zakat Nasional (Baznas) Kabupaten Gowa - Salmah, Salmah; Muin, Rahmawati; Wardy Putra, Trisno (MADINAH, 2021)
This study aims to determine the effectiveness of zakat management at BAZNAS in Gowa district. This type of research uses a qualitative approach with descriptive methods. Sources of data in this study are divided into 2, namely primary data and secondary data. Primary data in this study uses an instrument or questionnaire (questionnaire) which is a list of questions or statements prepared in writing, while secondary data is data that supports primary data obtained through documents. -company documents and reports that are relevant to this research. In the data collection process the methods used include 1) Observation, 2) Interview and, 3) Documentation. The results of the research show that the effectiveness of zakat management at BAZNAS in Gowa Regency covers several aspects, namely: planning, organizing, implementing and supervising.